Corrigendum/Addendum in ’Georgiades, F., 2018, Equilibrium Points with Their Associated Normal Modes Describing Nonlinear Dynamics of a Spinning Shaft with Non-Constant Rotating Speed, Journal of Vibration Testing and System Dynamics, 2(4), 327-373’ - Georgiades, Fotios (Journal of Vibration Testing and System Dynamics, 2026)
The form of the lower part of the vector eld erroneously leads to the conclusion/statement that the original system in 1st order has no linear counterpart, which is untrue. In here, the decomposition to linear and nonlinear part of the 1st order original system it is shown. The eigenvalues of the matrix associated with the linear part are all zero, therefore it cannot be claimed Lyapunov’s conclusion that the system in low energies can be approximated with the linear counterpart. Also, two typographic errors have been corrected. The corrections and the additions not only don’t affect the value of the rest part of the published article but also enhance the value of the original manuscript. More precisely, since the original system in low energies cannot be approximated by the solution of the linear counterpart, the followed approach to describe the dynamics of the spinning shaft with linearization around the equilibria of the restricted system which are the rigid body motions, is of higher significance.